Uma questão de incompletude / A matter of incompleteness - dos Santos, Mirian; Silvestre, Ana Carolina Faria (Revista Direito e Práxis, 2012)
DOI 10.12957/dep.2012.3053 Resumo Este artigo procura relacionar a incompletude da linguagem com a incompletude do sistema jurídico. Ambos lidam com a mobilidade. Para sustentar a nossa pesquisa, centramo-nos em teóricos da linguagem, tais como Santaella e Orlandi e teóricos do Direito como Castanheira Neves, Barak, Hart. Palavras-chaves: Incompletude. Linguagem. Sistema jurídico Abstract This article aims at relate the incompleteness of the language with the incompleteness of the legal system. And this incompleteness is due to the fact that both deal with mobility. To support our research, we focus on language theorists, such as Santaella and Orlandi and theorists of law as Castanheira Neves, Barak, Hart. Key words: Incompleteness. Language. Legal System